2005
DOI: 10.1111/j.1365-2109.2005.01333.x
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on the effects of dietary supplementation of brewers yeast and nucleotides, singularly or in combination, on juvenile red drum (Sciaenops ocellatus)

Abstract: This study was designed to evaluate the e¡ects of dietary supplementation with brewers yeast (Brewtech s ) and nucleotides (Optimu" n), either singularly or in combination, on red drum growth, body composition, stress responses and possible resistance to Amyloodinium ocellatum infection. Juvenile red drum ( $ 1g initially) fed practical ¢sh-meal-based diets for 6 weeks had similar weight gain regardless of whether the diet was unsupplemented (basal) or supplemented with brewers yeast (2% of diet), nucleotides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
66
2
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 40 publications
11
66
2
4
Order By: Relevance
“…The observed growth decline of fish fed high levels of soy bean and wheat proteins cannot be explained by reduced development of fillet muscles caused by lower protein retention or reduced fat storage. In contrast, other authors observed an influence of additives on crude lipid (Baruah et al, 2007;Li et al, 2005) or crude protein and lipid content (Abdel-Tawwab et al, 2008;Bagheri et al, 2008;Bairagi et al, 2004;Lara-Flores et al, 2003) in whole body composition. Additive and PP inclusion also did not influence HSI values and, consequently, did not seem to promote an increased or decreased fat retention in liver.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The observed growth decline of fish fed high levels of soy bean and wheat proteins cannot be explained by reduced development of fillet muscles caused by lower protein retention or reduced fat storage. In contrast, other authors observed an influence of additives on crude lipid (Baruah et al, 2007;Li et al, 2005) or crude protein and lipid content (Abdel-Tawwab et al, 2008;Bagheri et al, 2008;Bairagi et al, 2004;Lara-Flores et al, 2003) in whole body composition. Additive and PP inclusion also did not influence HSI values and, consequently, did not seem to promote an increased or decreased fat retention in liver.…”
Section: Discussionmentioning
confidence: 87%
“…Research demonstrated that b-glucan or MOS enriched diets did not improve growth in dentex (Dentex dentex), tilapia, Asian catfish (Clarias batrachus), channel catfish (Ictalurus punctatus), hybrid tilapia (O. niloticus ♀ × O. aureus ♂) and Atlantic salmon (Efthimiou, 1996;Grisdale-Helland et al, 2008;He et al, 2009;Kumari and Sahoo, 2006;Lara-Flores et al, 2003;Welker et al, 2007;Whittington et al, 2005). Moreover, supplementation with brown algae extracts, yeast nucleotides and potassium diformate did not support growth compared to the unsupplemented diets in red drum (Sciaenops ocellatus) and tilapia (Li et al, 2005;Merrifield et al, 2011;Zhou et al, 2009). Refstie et al (2010) proved that supplementation with MOS (2 g kg −1 diet) in a FM reduced diet, containing soy bean and sunflower meal (SBM + SFM) as substitutes, improved growth performance in salmon.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the yeast Saccharomyces cerevisiae has been found to be a good enhancer of the fish immune system (Siwicki et al, 1994). S. cerevisiae contains various immunostimulating compounds such as β-glucans, nucleic acids as well as oligosaccharides and it has the capability to enhance immune responses (Ortuno et al, 2002) as well as promoting growth (Li et al, 2004(Li et al, & 2005 of various fish species.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplementation of autolised yeast and zinc showed a positive interaction for Nile tilapia (Hisano et al, 2004). However, high levels of yeast in diets (as protein source) impaired not only growth performance (Furuya et al, 2000;Baccarin & Pezzato, 2001) but also physiological status (Runsey et al, 1991;Li & Gatlin III, 2003), probably due to high levels of non-protein nitrogen (Li & Gatlin III, 2004;Li et al, 2005).…”
Section: Resultsmentioning
confidence: 99%